Stress analysis of pin-loaded lugs using boundary element methods - Neo, Bernice Boon Siew (2017)
Stress and fracture analysis was carried out for an unflawed pin-loaded lug using Boundary Element Method (BEM). The effect of geometric parameter varies from the outer-to-inner radius ratio, angles of the loading and positioning of the pin-hole were studied. The location of the highest stress concentration factor was identified along the circumference of the pin hole where pressure is applied, giving two maximum tangential stress in each. Complete analysis shows that the direction of the loading and the outer-to-inner radius ratio have significant impact on the high concentration locations. With that, crack was modelled at those critical locations to analyze the stress intensity factors for different parameters used.